2022
DOI: 10.3389/fpls.2022.890980
|View full text |Cite
|
Sign up to set email alerts
|

A High-Quality Haplotype-Resolved Genome of Common Bermudagrass (Cynodon dactylon L.) Provides Insights Into Polyploid Genome Stability and Prostrate Growth

Abstract: Common bermudagrass (Cynodon dactylon L.) is an important perennial warm-season turfgrass species with great economic value. However, the reference genome is still deficient in C. dactylon, which severely impedes basic studies and breeding studies. In this study, a high-quality haplotype-resolved genome of C. dactylon cultivar Yangjiang was successfully assembled using a combination of multiple sequencing strategies. The assembled genome is approximately 1.01 Gb in size and is comprised of 36 pseudo chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 85 publications
(105 reference statements)
2
6
0
Order By: Relevance
“…Further analysis revealed that 97.5% of Illumina short reads were mapped to our genome assembly, with a base-level accuracy of 99.5%. At the whole-genome level, BUSCO (Sim O et al, 2015) evaluation revealed that 97.3% of the set consisted of 1614 complete BUSCO genes (Table 1; Table S4), which is similar to the percentages reported in C. transvaalensis (2n = 2x = 18) (Cui et al, 2021) and Yangjiang (C. dactylon 'Yangjiang') (Zhang et al, 2022), implying that our bermudagrass assembly is complete. The assembly's completeness and contiguity were also verified using the LTR assembly index (LAI) .…”
Section: Cynodon Dactylon Genome Assembly and Annotationsupporting
confidence: 74%
“…Further analysis revealed that 97.5% of Illumina short reads were mapped to our genome assembly, with a base-level accuracy of 99.5%. At the whole-genome level, BUSCO (Sim O et al, 2015) evaluation revealed that 97.3% of the set consisted of 1614 complete BUSCO genes (Table 1; Table S4), which is similar to the percentages reported in C. transvaalensis (2n = 2x = 18) (Cui et al, 2021) and Yangjiang (C. dactylon 'Yangjiang') (Zhang et al, 2022), implying that our bermudagrass assembly is complete. The assembly's completeness and contiguity were also verified using the LTR assembly index (LAI) .…”
Section: Cynodon Dactylon Genome Assembly and Annotationsupporting
confidence: 74%
“…Here, to explore effectual phased tools and strategies for assembling complex plant genomes, we have summarized the recently published haplotype-resolved assemblies in plant genomes. We have further divided these assembly approaches into two strategies: reference-based variant phasing and de novo assembly-based haplotype phasing ( Table 1 ) [12] , [51] , [14] , [15] , [16] , [17] , [18] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] .…”
Section: Toward Haplotype-resolved Assemblymentioning
confidence: 99%
“…Bermudagrass contains many allelochemicals such as Caffeic, Ferulic, P-Coumaric, P-Hydroxybenzoic Syringic Acids and Vanillic (Mahmoodzadeh, 2010). These phenolics represent the effect of allelopathy which supports the statement that phytotoxicity of bermudagrass may be because of the occurrence of phenolic compounds (Zhang et al, 2022). Experiments under laboratory are thought to be indispensable and useful to investigate the allelopathic potential of any plant (Tibugari et al, 2020).…”
Section: Introductionmentioning
confidence: 82%
“…Bermudagrass (Cynodon dactylon L.) is well known as worst weed that is found almost everywhere in the world and it consists of the fourth most allelopathic compounds (Zhang et al, 2022). Due to its compatibility for water, nutrients, space and the soil oxygen, bermudagrass is often an effective colonizer (Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%